2021
DOI: 10.3390/land10090983
|View full text |Cite
|
Sign up to set email alerts
|

The Heightened ‘Security Zone’ Function of Gated Communities during the COVID-19 Pandemic and the Changing Housing Market Dynamic: Evidence from Beijing, China

Abstract: The ongoing COVID-19 pandemic has left a strong imprint on many aspects of urban life. Gated communities (GCs) in China are less commonly perceived as a negative and segregated urban form of community compared to other contexts, owing to their wide variety and relative openness. Yet, the enhanced security zone function and the popularity of GCs, along with the heightened segregation and exclusion effects, mean they are most likely to emerge in post-pandemic urban China because of the perceived effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The study by Cigdem-Bayram and Prentice (2019) in two Australian cities of Melbourne and Victoria revealed that there is inverse association between crime and housing prices in regional Victoria but with no effects in Melbourne. Li et al (2021) reported the heightened security problem in China and its impacts on home prices in Beijing. The researchers found that security is much related to home prices in the Beijing metropolitan area.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Cigdem-Bayram and Prentice (2019) in two Australian cities of Melbourne and Victoria revealed that there is inverse association between crime and housing prices in regional Victoria but with no effects in Melbourne. Li et al (2021) reported the heightened security problem in China and its impacts on home prices in Beijing. The researchers found that security is much related to home prices in the Beijing metropolitan area.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…Urban insecurity issues including crimes, violence and assaults are neighborhood-location specific problems that may have adverse effects on urban residents and housing prices. While some of the neighborhood specific factors such as proximity to transport routes, shopping malls, children schools may have positive effects on property values many of the neighborhood specific factors such as flood risk, insecurity, violence or crime constitute negative externalities that adversely affect prices of real estate (Huth, 1981;Ceccato and Wilhelmsson, 2011;Buonanno et al, 2012;Naghibi et al, 2015;Hsu et al, 2016;Mcllhatton et al, 2016;Bako et al, 2018;Tillyer and Walter, 2018;Beltran et al, 2019;Song et al, 2019;Cigdem-Bayram and Prentice, 2019;Senick, 2019;Wong et al, 2019;Bamiteko and Adebiyi, 2020;Payne and Daryol, 2020;Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this argument started to take another direction as a result of the current COVID-19 pandemic, with various studies suggesting that gated communities may become more popular after the pandemic, which is perhaps reflected by the increasing price of housing units within these communities. For example, the perceived advantage of greater security has already had a significant impact on the housing prices in China, reflected by an increase of 2% compared to the non-gated communities [ 19 ]. Residents believe that these communities are effective in pandemic risk reduction in terms of limiting outsider access, which creates a kind of ‘security zone’.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Residents believe that these communities are effective in pandemic risk reduction in terms of limiting outsider access, which creates a kind of ‘security zone’. However, there is a lack of direct medical evidence to conclude that gated communities are more effective in reducing the risk of COVID-19 infection [ 19 ]. In fact, Seanders and Maroofi [ 20 ] investigated the impact of gated communities on the spread of COVID-19 with reference to Jakarta, Indonesia, with the authors claiming that gated communities have the potential to slow down the spread of COVID-19 virus due to their relative self-sufficiency.…”
Section: Literature Reviewmentioning
confidence: 99%